Rationality of Economic Nature Use as a Transboundary Problem: Legal Approach - Nadezhda M. Mityakina, Aleksey S. Fedoryaschenko, Yuliya V. Boltenkova,; Marina S. Sorokoletova, Vladimir S. Sinenko, (Opción)
The article considers the legal approach to the rational economic management of nature from the standpoint of the global nature of this problem. At the end of the study, the conclusion is made that rational nature management should be the main paradigm (basic fundamental rule) of the exploitation of natural objects in entrepreneurial activity. Rationality in the use of natural resources includes two aspects: economic (the possibility of exploiting nature, its consumption, ensuring sustainable economic growth) and actually ecological (preserving natural objects, their reproduction, avoiding causing harm to the environment). In this case, both sides coexist together and must be balanced.